DEVELOPMENT OF PCR BASED METHODS FOR DETECTION OF POTATO AUCUBA MOSAIC VIRUS IN INDIA - Kumar, Ravinder; A, Jeevalatha; Sharma, N N; Sharma, Sanjeev; Chakrabarti, S K; Singh, B P (Potato Journal, 2015)
Potato aucuba mosaic virus (PAMV) is a common virus of potato crop. A high incidence of PAMV was recorded in the last decade and is since becoming a threat to the Indian seed potato production programme. Enzyme-linked immunosorbent assay (ELISA) is normally adopted for indexing of tubers and micropropagated potato plants for viruses but it could not detect PAMV due to its low titer. Therefore, six sets of primers were designed for RT-PCR amplification of conserved areas in 26kDa protein, RNA polymerase and coat protein genes of PAMV. Reverse transcription polymerase chain reaction (RT-PCR) and one step immunocapture RT-PCR (IC-RT-PCR) methods were developed for detection of PAMV from leaves and tubers. The protocols could be used for epidemiological studies, routine testing and virus indexing of mother stocks as well as for healthy seed potatoes production programme.